SAT0346 Risk Characterisation Methodology Enabling Safety Comparisons Between Tofacitinib and Tumour Necrosis Factor Inhibitors. (9th June 2015) - Curtis, J.R.; Klareskog, L.; Zhang, R.; Krishnaswami, S.; Anisfeld, A.; Chen, Y.; Geier, J.
Abstract : Background: Tofacitinib is an oral JAK inhibitor for the treatment of RA. For new therapies, it is important to contextualise safety with established therapies such as TNF inhibitors (TNFi). Analyses were conducted based on the projected patient-years (PY) of accrual within the pooled Phase 2, Phase 3 and long-term extension (P2P3LTE) tofacitinib rheumatoid arthritis (RA) studies and external data for TNFi. Objectives: To estimate the minimum threshold for detecting risk of specific adverse events (i.e., serious infections, all malignancies [excluding non-melanoma skin cancer (NMSC)], NMSC, major adverse cardiovascular endpoints [MACE], opportunistic infections [OI], lymphoma and gastrointestinal [GI] perforations) based on PY available for tofacitinib. Methods: Power calculations were conducted based on a Poisson distribution to estimate the minimum PY of exposure needed to have 90% probability that the lower bound of the confidence interval (CI) for tofacitinib minus TNFi will be >1, for true tofacitinib rates of 1.2×, 1.5× or 2.0× the comparator rates. Rates of events for TNFi were derived from sources (i.e., published clinical trials and observational studies) intended to optimise similarity to the tofacitinib clinical trial database in term of baseline characteristics, study duration and average patient follow-up time. Results: Based on projections, approximately 18, 000 PY of exposure to tofacitinib will be accrued within the RA BID clinical development programme; the majority of these data will come from patients treated for at least 3 years. Table 1 highlights the PY of exposure needed to detect an increased risk in safety events as compared with published TNFi rates. Conclusions: The risk characterisation approach represents an indirect method to contextualise the safety profile of tofacitinib as compared with TNFi. Ongoing and planned prospective active surveillance complement the data generated from clinical trials. References: Askling J, Baecklund E, Granath F, et al. Ann Rheum Dis 2009;68(5):648-53. Gout T, Ostör AJ, Nisar MK. Clin Rheumatol 2011;30(11):1471-4. Keystone EC, van der Heijde D, Kavanaugh A, et al. J Rheumatol, 2013. 40(9):1487-97. Mariette X, Matucci-Cerinic M, Pavelka K, et al. Ann Rheum Dis 2011. doi: 10.1136/ard.2010.149419. Winthrop KL. Rheum Dis Clin Am, 2012;38:727-645. Disclosure of Interest: J. Curtis Grant/research support from: Pfizer, Inc., L. Klareskog: None declared, R. Zhang Shareholder of: Pfizer, Inc., Employee of: Pfizer, Inc., S. Krishnaswami Shareholder of: Pfizer, Inc., Employee of: Pfizer, Inc., A. Anisfeld Shareholder of: Pfizer, Inc., Employee of: Pfizer, Inc., Y. Chen Shareholder of: Pfizer, Inc., Employee of: Pfizer, Inc., J. Geier Shareholder of: Pfizer, Inc., Employee of: Pfizer, Inc.